Chemical Characterization of the American Oil Palm from the Brazilian Amazon Forest. Issue 5 (12th July 2018) - España, Maria Daniela; Mendonça, Simone; Carmona, Paula Andrea Osorio; Guimarães, Marina Borges; da Cunha, Raimundo Nonato Vieira; Souza, Manoel Teixeira
Abstract : American oil palm [ Elaeis oleifera (Kunth) Cortes] is known to present a much slower palm oil deterioration rate than African oil palm ( E. guineensis Jacq.). In the present study, fatty acid composition, total carotenoids, oil content, and free fatty acid content were characterized for five accessions (Careiro, Anori, Manicoré, Coari, and Autazes) belonging to an American oil palm collection maintained as field gene bank by Embrapa. This germplasm collection was originally collected in different areas in the Brazilian Amazon forest. These accessions were subjected to different storage times (1, 7, and 14 d) before processing to evaluate the quality of the oil produced. Oil content of the dried pulp was found to range between 31.36 and 50.34%. Gas chromatographic analysis revealed that oleic acid is the predominant monounsaturated fatty acid in all five accessions. After 14 d of fruit storage, these accessions were found to maintain low acidity (free fatty acid content), between 1.33 and 2.66%. Total carotenoid content was presented in high concentrations in all five accessions (>1500 mg kg −1 ). The estimation of genetic parameters showed, in general, high heritability values (>80%), and the estimated genetic gains were generally very high. Coari and Careiro presented the highest oil yields, whereas Manicoré and Coari presented the lowest acidity. These two characteristics are the most important ones when selecting the best parental donor to develop superior interspecific hybrids.